Change and continuity in Ghana's intellectual history: From late 19th century to the eras of decolonisation and independence. Issue 4 (2nd October 2019) - Boadu, Gideon
ABSTRACT: This article explores intellectual growth and development in Gold Coast/Ghana from the late 19 th century through the period of decolonisation to the emergence of the country as a post-independence state. It begins with a brief description of some of the key texts written within each of the three periods. Then with focus on three key intellectual historians, Carl Christian Reindorf, Kobina Sekyi, and Kwame Nkrumah, it examines the changes and continuities that characterised specific texts produced across the periods, using three themes as the connecting threads. The article explains that the early intellectual efforts provided a conduit for further intellectual explosion, particularly, within the domain of historical study.